Breastfeeding pattern based on nutritional status in 6-12 months old infants - Carissa Cerdasari (Berita Kedokteran Masyarakat (BKM), 2018)
Background: Malnutrition especially undernutrition is still concern for public health problems.Underweight in children will disrupt the learning process due to interference with the development of intelligence, more susceptible to infection and increase disease severity, to increase mortality. Objective: This study was conducted to asses the difference breastfeeding patterns include the breastmilk only duration and daily breastfeeding frequencies based on nutritional status in 6-12 months old infants. Methods: In this cross-sectional study, mothers (n=60) of infants aged 6-12 months old were recruited. The infant’s nutritional status was determined anthropometrically by 3 indexes ie body weight for age, length for age, and weight for length. Breastfeeding patterns include the breastmilk only duration and daily breastfeeding frequencies is obtained by interview and by 2x24 hour daily breastfeeding form. Kruskal-wallis test were used to evaluate the difference breastfeeding patterns based on nutritional status. Results: The average of brestmilk only duration was 3,21±2,41 months, and the average of daily breastfeeding frequencies was 12,46±3,8 times a day. Most of the respondents were in normal nutritional status (86,67% for W/A, 83,3% for L/A, and 85,0% for W/L). There were no difference in breastfeeding patterns either on breastmilk only durations or on daily breastfeeding frequencies based on nutritional status in 6-12 months old infants (p>0,05).Conclusion: Infant's nutritional status is determined more by the daily energy consumption of all infant foods, not only from breastmilk but also from complementary food.